Fuel Control Systems for Planetary Transmission Vehicles: A Contribution to the LPG-fueled Vehicles Community - Suroto Munahar; Bagiyo Condro Purnomo; Hasan Köten (Universitas Muhammadiyah Magelang, 2021)
The bi-fuel system vehicle (gasoline/LPG) has been developed for a long time because it has the ability to switch fuels, both built as an original equipment manufacturer (OEM) or as a modified vehicle. However, on vehicles with planetary automatic transmissions, additional control systems are needed to produce optimal performance, both on gasoline and LPG operations, especially on uphill roads. Old vehicles with planetary automatic transmissions are not equipped with road slope angle sensors, so on uphill roads and the driver has not mastered road conditions, the engine tends to stop suddenly. Therefore, this study aims to develop a fuel control system (LPG operation) on a planetary automatic transmission to control gear shifts based on the level of the road slope. A simulation with MATLAB Simulink we used to create a control system, with objective function and constraint defined. As a result, the control system can recognize the level of the road slope to control the speed gear shift. This control system is promising and reliable to be implemented in real conditions.